Grabbing the Bull by Both Horns: Bovine Ultralong CDR-H3 Paratopes Enable Engineering of ‘Almost Natural’ Common Light Chain Bispecific Antibodies Suitable For Effector Cell Redirection - Klewinghaus, Daniel; Pekar, Lukas; Arras, Paul; Krah, Simon; Valldorf, Bernhard; Kolmar, Harald; Zielonka, Stefan (Frontiers in Immunology, 2022)
A subset of antibodies found in cattle comprises ultralong CDR-H3 regions of up to 70 amino acids. Interestingly, this type of immunoglobulin usually pairs with the single germline VL gene, V30 that is typically very conserved in sequence. In this work, we have engineered ultralong CDR-H3 common light chain bispecific antibodies targeting Epidermal Growth Factor Receptor (EGFR) on tumor cells as well as Natural Cytotoxicity Receptor NKp30 on Natural Killer (NK) cells. Antigen-specific common light chain antibodies were isolated by yeast surface display by means of pairing CDR-H3 diversities following immunization with a single V30 light chain. After selection, EGFR-targeting paratopes as well as NKp30-specific binders were combined into common light chain bispecific antibodies by exploiting the strand-exchange engineered domain (SEED) technology for heavy chain heterodimerization. Biochemical characterization of resulting bispecifics revealed highly specific binding to the respective antigens as well as simultaneous binding to both targets. Most importantly, engineered cattle-derived bispecific common light chain molecules elicited potent NK cell redirection and consequently tumor cell lysis of EGFR-overexpressing cells as well as robust release of proinflammatory cytokine interferon-γ. Taken together, this data is giving clear evidence that bovine bispecific ultralong CDR-H3 common light chain antibodies are versatile for biotechnological applications.